EVALUASI MANAJEMEN KEUANGAN PENDIDIKAN ISLAM METODE IMPORTANCE PERFORMANCE ANALYSIS : Studi Kasus Komite SMA Cendekia Bekasi - Dianing Sapitri; Endin Mujahidin; Nesia Andriana (Universitas Islam Negeri Alauddin Makassar, 2023)
Islamic education financial management must be the concentration of the school in meeting the financing needs of the education. The purpose of this study was to analyze the level of satisfaction and the interests or expectations of students' guardians in the service and financial management of Islamic education at SMA Cendekia to evaluate future development. The method used in this study is a mix method with a sequential explanatory strategy, namely by conducting a quantitative analysis of the Importance Performance Analysis (IPA) method to find the level of importance and performance of school financial management then the findings are analyzed using qualitative methods to produce research conclusions. The results showed; (1) It is important for schools to communicate with student guardians, alumni, and the community in assisting the fulfillment of funding sources. (2) The importance of paying attention and understanding the financial problems experienced by students. From these two findings, it is hoped that schools can build collaboration with more active and creative committees to help communicate financial issues to achieve quality Islamic education.